An approach for finite strains and rotations of shells of revolution with application to a spherical shell under a uniformly distributed pressure - Erdölen, A; Yükseler, RF (SAGE PUBLICATIONS LTD, 2003)
A theoretical and numerical analysis of rubber-like shells of revolution undergoing finite strains and finite rotations with the application to the problem of a spherical shell subject to a uniformly distributed internal pressure is presented. The comparison of the results corresponding to two different definitions proposed for the reference surface of deformed rubber-like shells, an asymptotical solution, and the membrane solution is presented, as well.
Keywords: rubber-like shells; finite strains; finite rotations; shell; Materials Science; Polymer Science